Grassroots memorials : the politics of memorializing traumatic death - Margry, P. J. (Peter Jan); Sánchez Carretero, Cristina (Remapping cultural history ;, 2011)
Grassroots memorials have become major areas of focus during times of trauma, danger, and social unrest. These improvised memorial assemblages continue to display new and more dynamic ways of representing collective and individual identities and in doing so reveal the steps that shape the national memories of those who struggle to come to terms with traumatic loss. This volume focuses on the hybrid quality of these temporary memorials as both monuments of mourning and as focal points for protest and expression of discontent. The broad range of case studies in this volume include anti-mafia shrines, Theo van Gogh's memorial, September 11th memorials, March 11th shrines in Madrid, and Carlo Giuliani memorials in Genoa.